Análisis de la auditoría forense cómo método de prevención del fraude en las Cooperativas de Ahorro y Crédito del Distrito Metropolitano de Quito en el 2012-2013 - Sarango Condolo, María Yolanda (2014)
In the present investigation seeks to understand the Forensic Audit as prevention of fraud, starting from basic concepts, methods and tools used this new branch of the audit for the detection, prevention and monitoring of financial crimes, the same that have increased in recent years and which has been used to forensic audit as control system, control and investigación.Una once understood and studied the basics of this audit we will focus the situational analysis of the ivas Cooperat Savings and Credit District Metropolitano de Quito